(Bio)sensores eletroquímicos impressos em 3d e novos filamentos condutivos aplicados à química analítica - Silva, Luiz Ricardo Guterres e (Universidade Federal de São Carlos, 2024)
Electrochemical sensors can be employed for diverse detection purposes, and their modification with biological compounds enables the development of biosensors with selectivity for analytes such as viruses. Furthermore, the manufacturing of electrochemical sensors with a focus on miniaturization and cost reduction is of paramount importance for producing efficient analytical platforms. In this context, 3D printing technology facilitates the rapid, decentralized, and miniaturized production of sensors using conductive filaments. Therefore, this thesis presents the fabrication of conductive filaments and 3D (bio)sensors using both laboratory-made and commercial filaments for the detection of biomarkers and viruses, specifically SARS-CoV-2 and Monkeypox virus (MKPV). All developed materials and sensors underwent characterization through morphological, physicochemical, and electrochemical techniques. The (bio)sensors for creatinine and SARS-CoV-2 cDNA exhibited a detection limit (LD) of 15.0 and 0.31 µmol L−1, respectively. Sensors produced from the new filaments (graphite and carbon black) demonstrated satisfactory electrochemical characteristics compared to sensors produced with commercial filaments. The application of 3D graphite-based (bio)sensors for the determination of uric acid and SARS-CoV-2 S1 protein show LD values of 0.07 and 1.36 nmol L−1, respectively. The carbon black-based biosensor indicated a LD of 2.7 pmol L−1 for S1 protein. For MKPV detection, a multiplex device based on an immunosensor and a genossensor showed LD values of 2.9 and 27.0 nmol L−1 for A29 protein and DNA, respectively. All recovery tests exhibited values close to 100%. Consequently, 3D sensors prove to be a highly potent tool for virus detection and their biomarkers. The laboratory production of conductive filaments enabled the construction of excellent sensors using diverse materials, providing a viable alternative to commercial options.
3D printed electrochemical (bio)sensors and new conductive filaments applied to analytical chemistry
Keywords: Impressão 3D; Filamentos condutivos feitos em laboratório; (Bio)sensores eletroquímicos; Detecção de vírus; SARS-CoV-2; Varíola dos macacos; 3D printing; Lab-made conductive filaments; Electrochemical (bio)sensors; Virus detection; SARS-CoV-2; Monkeypox virus; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA